Historical textiles and their characterization - Rezić, Iva (Cambridge Scholars Publishing, 2022)
This book utilizes current scientific advances to better understand the principles of degradation of historical textile materials (including ancient mummies, dresses, jewellery and musical instruments) and their characterisation. Moreover, it highlights the importance of multidisciplinary procedures as a part of complex task when only a relatively low amount of materials are available for analysis. In such cases, only sensitive, selective and reliable analytical procedures, such as microscopy, spectroscopy and chromatography, can be applied in the characterization of precious materials.As this book explores current scientific advances to better understand the principles of materials characterisation, it is of broad general interest to the general public, but also to the chemical, anthropological and conservation-restoration communities. Moreover, it also offers particular support to a global audience interested in the preservation of historical materials.00Iva Rezic, PhD, served as Vice-Dean for Scientific Research at the Faculty of Textile Technology of the University of Zagreb, Croatia, where she leads a group of scientists in the field of chemical analysis and material sciences. Her research focuses on both natural sciences (analytical chemistry) and technical sciences (materials engineering), with a particular interest in the development of new materials and analysis of old and precious samples. She is the author of 56 scientific papers, three university textbooks and five book chapters.